Vietnam Report on the Observance of Standards and Codes : Accounting and Auditing Module - World Bank (Hong Duc Publishing House, Hanoi, 2017)
Vietnam's rapid economic growth since the late 1980s has brought it quickly to middle income–country status, a performance surpassed only by China. This growth has slowed in recent years, however, due to the weaker external environment and a slowdown in reforms. Vietnam has the potential to join the ranks of upper middle income countries in the next twenty years, but this will require tough choices and actions to deepen market institutions, create a level playing field for the private sector and the state-owned enterprises (SOEs), and build a modern financial sector. Vietnam is embarking on a process of implementing a broad range of reforms designed to realize its aspiration of becoming high-income country. As outlined in the recently published World Bank report 'Vietnam 2035', Vietnam compares well with upper-income-countries in Government effectiveness and political stability, but ranks poorly for voice and accountability and regulatory quality (which measures the perceptions of the capacity of the state to formulate and implement policies aimed at private-sector development).